2003
DOI: 10.1046/j.1365-2125.2003.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and systemic effects of inhaled fluticasone propionate in chronic obstructive pulmonary disease

Abstract: AimsWe have previously shown that the systemic exposure to inhaled fluticasone propionate (FP) is reduced in asthmatics compared with healthy subjects. We have now compared its pharmacokinetics in patients suffering from chronic obstructive pulmonary disease (COPD, n = 10) and matched healthy subjects ( n = 13). Methods A double-blind, randomized, cross-over study design was used. Plasma FP and serum cortisol were measured for 12 h after subjects received hydrofluoroalkane FP 1000 m g day -1 inhaled (via an MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…Patient-specific factors such as age (29,30), height (30), and sex (31) have also been demonstrated to influence particle deposition patterns and/or the PK after drug inhalation. Airway diseases (e.g., asthma bronchiale or COPD) and even different disease stages altered the particle deposition patterns (32): The total bioavailability of fluticasone propionate (33)(34)(35) was decreased in patients with more severe asthma bronchiale and COPD. Similarly, maximum plasma concentrations and the exposure were decreased for inhaled fluticasone propionate and budesonide after provoking bronchoconstriction (decreased forced expiratory volume in 1 s (FEV1)) in asthma patients (36).…”
Section: Pulmonary Particle/droplet Deposition Patternsmentioning
confidence: 99%
“…Patient-specific factors such as age (29,30), height (30), and sex (31) have also been demonstrated to influence particle deposition patterns and/or the PK after drug inhalation. Airway diseases (e.g., asthma bronchiale or COPD) and even different disease stages altered the particle deposition patterns (32): The total bioavailability of fluticasone propionate (33)(34)(35) was decreased in patients with more severe asthma bronchiale and COPD. Similarly, maximum plasma concentrations and the exposure were decreased for inhaled fluticasone propionate and budesonide after provoking bronchoconstriction (decreased forced expiratory volume in 1 s (FEV1)) in asthma patients (36).…”
Section: Pulmonary Particle/droplet Deposition Patternsmentioning
confidence: 99%
“…As recently shown by Singh et al (2003), the mean (range) systemic availability of a single 1000-g inhaled dose of FTP was 21.2% (14.3-31.4%) and 13.3% (8.5-20.9%) in healthy controls and adults with chronic obstructive pulmonary disease, respectively. Thus, when a therapeutic dose of FTP is delivered to the airway under controlled circumstances (e.g., supervised, proper administration techniques), greater then negligible systemic exposure may result.…”
Section: Discussionmentioning
confidence: 75%
“…to increase the extent of systemic drug exposure over that predicted from its innate pharmacokinetic characteristics (Singh et al, 2003). Using the CYP3A4/5 substrate alfentanil, Klees et al (2005) demonstrated that ketoconazole (a commonly used azole antifungal agent) was an order of magnitude more potent than troleandomycin as an inhibitor of CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations